STOP & STARE: STUDI KASUS PERILAKU PENGGUNA RUANG DURIAND BINTARO - Muhammad Haidir Rapiq; Edhy Prabowo; Hanifa Fijriah Wasnadi (ITB Ahmad Dahlan Jakarta, 2021)
Durian specialty restaurant is a restaurant that sells a variety of durians and souvenirs. One of the durian specialty restaurants is DuriAnd Bintaro. In the way of payment and order, the Quality Control stage is a unique part of this restaurant. This stage presents a pattern of behavior that is different from other restaurants. There is a special ‘talented’ restaurant staff at the Quality Control table to recommend the perfect durian to be purchased. In the other hand, this stage affects the rest of order and payment method. The Quality Control stage takes a lot of time which can result in customer buildup in the space, waiting for their turn to order. However, this stage is an important part because it will decide the quality of the durian that customers will eat. Qualitative research methods with literature studies, visits and interviews were carried out to analyze behaviors of all related actors. The study found that space that holds “stop & stare” activity during quality control stage in similar restaurant needs to consider the room size and interior layout to accommodate the situation.